ARTIFICIALLY INTELLIGENT CHATBOTS FOR HIGEREDUCATION: A REVIEW OF EMPIRICAL LITERATURE - Momonov, Galymzhan (Journal of Emerging Technologies and Computing, 2024)
This paper reviews empirical literature on artificially intelligent chatbots for higher education published in 2000-2021 in peerreviewed journals. The review shows that chatbots are mainly used for teaching assistance and for non-academic support purposes. The published studies unanimously report positive effects of chatbots on the outcomes of interest. The review suggests that chatbots have a considerable potential to be used more widely in higher education. Further, the research on chatbots in higher education is ripe for more research.